Baseline susceptibility of Philippine Ostrinia furnacalis (Lepidoptera: Crambidae) populations to insecticidal Cry1A.105 and Cry2Ab2 proteins and validation of candidate diagnostic concentration for monitoring resistance - Edwin Alcantara; MARNELLE M. ATIENZA; LUIS CAMACHO; SRINIVAS PARIMI (Society for Indonesian Biodiversity, 2021)
Abstract. Alcantara EP, Atienza MM, Camacho L, Parimi S. 2021. Baseline susceptibility of Philippine Ostrinia furnacalis (Lepidoptera: Crambidae) populations to insecticidal Cry1A.105 and Cry2Ab2 proteins and validation of candidate diagnostic concentration for monitoring resistance. Biodiversitas 22: 956-960. This study estimated the baseline susceptibility of Ostrinia furnacalis populations from the Philippines, to purified insecticidal Cry1A.105 and Cry2Ab2 proteins and determined a diagnostic concentration (DC) through a validation experiment. The insect populations were collected from separate sites of corn farms in Northern and Central Luzon and in South Cotabato province of the island of Mindanao. Dose-response bioassays using artificial diet surface overlay method were conducted on eight populations. The bioassay results revealed that the LC50 of Cry1A.105 and Cry2Ab2 to O. furnacalis ranged from 0.03 ng/cm2 to 0.18 ng/cm2 and 1.40 ng/cm2 to 9.98 ng/cm2, respectively. The relative susceptibility ratios between the most susceptible and most tolerant populations were 6-fold for Cry1A.105 and about 7-fold for Cry2Ab2. The candidate diagnostic concentrations (DC) based on the LC99 were calculated using the baseline bioassay data for both Cry1A.105 and Cry2Ab2. The validation was performed on populations from the same locations used in the baseline susceptibility assay and a reference strain to produce at least 99% mortality for each protein. Data showed that populations tested with Cry1A.105 produced average mortality of at least 99% for the upper limit, while this was observed in the LC99 estimate for Cry2Ab2. The validated diagnostic concentration can be used for monitoring the resistance development of O. furnacalis exposed to Bt Corn, MON89034, in the Philippines.